Bimetallic Metal-Organic Framework-Derived Carbon Nanotube-Based Frameworks for Enhanced Capacitive Deionization and Zn-Air Battery - Shi, Wenhui; Xu, Xilian; Ye, Chenzeng; Sha, Dongyong; Yin, Ruilian; Shen, Xuhai; Liu, Xiaoyue; Liu, Wenxian; Shen, Jiangnan; Cao, Xiehong; Gao, Congjie (Frontiers in Chemistry, 2019)
Carbon-based materials have attracted intensive attentions for a wide range of energy and environment-related applications. Energy storage/conversion devices with improved performance have been achieved by utilization of metal-organic-framework (MOF)-derived carbon structures as active materials in recent years. However, the effects of MOF precursors on the performance of derived carbon materials are rarely investigated. Here, we report that the incorporation of small amount of Fe or Ni in Co-based MOFs leads to a significant enhancement for the derived carbon nanotube-based frameworks (CNTFs) in Na+/Cl− ion electrosorption. Further investigation revealed the enhanced performance can be attributed to the improved specific surface area, electrical conductivity, and electrochemical activity. Notably, the CoFe-CNTF derived from bimetallic CoFe-MOFs achieves a high ion adsorption capacity of 37.0 mg g−1, superior to most of recently reported carbon-based materials. Furthermore, the CoFe-CNTF also demonstrates high catalytic activity toward oxygen evolution reaction (OER) with a Tafel slope of 87.7 mV dec−1. After combination with three-dimensional graphene foam (3DG), the resultant CoFe-CNTF-coated 3DG is used as air-cathode to fabricate a flexible all-solid-state Zn-air battery, which exhibits a high open circuit potential of 1.455 V. Importantly, the fabricated flexible battery can light a light-emitting diode (LED) even when it is bent. This work provides new insights into designs of high-performance and flexible electrode based on MOF-derived materials.